penyelesaian sengketa waris (menurut hukum adat minangkabau dan hukum islam - RAMA DEYAN; Teuku Yudi Afrizal; Hamdani H (Fakultas Hukum Universitas Malikussaleh, 2021)
Minangkabau Customary Inheritance Law, that heirlooms in customary provisions are passed on to maternal offspring (matrilineal), who adhere to the collective or communal principle, namely common ownership. While in Islamic inheritance adheres to the principle of individual, meaning that each heir has the right to own it individually without being bound by others. The purpose of this study is to find out the process of resolving disputes over the division of inheritance in Minangkabau Customary Law and Islamic Law and obstacles in the implementation in Nagari Tanjung Barulak District of Batipuh Tanah Datar District of West Sumatra Province. The research method used in this study is empirical juridical research methods with a library and field approach. The library approach is used to obtain theoretical secondary data, while the field approach is used to obtain primary data through an interview process with respondents and informants. The results of this study found that the settlement of inheritance disputes in Minangkabau Customary law was carried out in the implementation attended by the heirs, niniak mamak and datuak in their respective people. The decision-making process through deliberations, settlement of inheritance in Minangkabau there are several obstacles that make the settlement unresolved, namely the factors of the Minangkabau customary family relations system, the economy of the heirs, and the involvement of niniak mamak in the process of inheritance reform. The barriers to the division of inheritance in Islam in the minangkabau indigenous people, especially in Nagari Tanjung Barulak theyt state that the division of inheritance customarily is in accordance with Islamic inheritance, but in reality in its implementation is not in accordance with Islamic inheritance.